A comparative analysis of the mutagenicity of platinum-containing chemotherapeutic agents reveals direct and indirect mutagenic mechanisms. (27th January 2021) - Szikriszt, Bernadett; Póti, Ádám; Németh, Eszter; Kanu, Nnennaya; Swanton, Charles; Szüts, Dávid
Abstract: Platinum-based drugs are a mainstay of cancer chemotherapy. However, their mutagenic effect can increase tumour heterogeneity, contribute to the evolution of treatment resistance and also induce secondary malignancies. We coupled whole genome sequencing with phenotypic investigations on two cell line models to compare the magnitude and examine the mechanism of mutagenicity of cisplatin, carboplatin and oxaliplatin. Cisplatin induced significantly more base substitution mutations than carboplatin or oxaliplatin when used at equitoxic concentrations on human TK6 or chicken DT40 cells, and also induced the highest number of short insertions and deletions. The analysis of base substitution spectra revealed that all three tested platinum drugs elicit both a direct mutagenic effect at purine dinucleotides, and an indirect effect of accelerating endogenous mutagenic processes, whereas the direct mutagenic effect appeared to correlate with the level of DNA damage caused as assessed through histone H2AX phosphorylation and single-cell agarose gel electrophoresis, the indirect mutagenic effects were equal. The different mutagenicity and DNA-damaging effect of equitoxic platinum drug treatments suggest that DNA damage independent mechanisms significantly contribute to their cytotoxicity. Thus, the comparatively high mutagenicity of cisplatin should be taken into account in the design of chemotherapeutic regimens.